On the best approximation of periodic functions of two variables by polynomial splines - Korneichuk, N. P. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We consider the problem of the best approximation of periodic functions of two variables by a subspace of splines of minimal defect with respect to a uniform partition.